Systematic Literature Review of Intellectual Capital in State-Owned Enterprises (BUMN) - Indria Sari; Rika Gamayuni, Rindu; Asmaranti, Yuztitya (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to systematically review the literature on Intellectual Capital (IC) within the context of State-Owned Enterprises (SOEs) during the period of 2020 to 2025. Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, this article analyzes 30 indexed scientific journals relevant to the topic of IC and SOEs. The analysis reveals that Human Capital Efficiency (HCE) is the most dominant IC component influencing organizational performance, followed by Capital Employed Efficiency (CEE). The reviewed studies also indicate a growing trend in the use of the Value Added Intellectual Coefficient (VAIC) model and the increasing integration of IC with aspects of corporate governance (GCG), corporate social responsibility (CSR), and environmental uncertainty. Indonesia is recorded as the country with the highest number of related publications, followed by China and Italy. Although publication trends showed a significant increase during 2021–2022, qualitative research and multidimensional approaches to Relational Capital remain limited. This study recommends further exploration through longitudinal methods and cross-country comparisons to broaden the understanding of IC management in the public sector.